2018
DOI: 10.1007/s40266-018-0610-y
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran Versus Rivaroxaban for Secondary Stroke Prevention in Patients with Atrial Fibrillation Rehabilitated in Skilled Nursing Facilities

Abstract: Background: Thromboembolic and bleeding risk are elevated in older patients with atrial fibrillation and prior stroke. We compared dabigatran versus rivaroxaban for secondary prevention in a national population after skilled nursing facility (SNF) discharge. Methods: Medicare fee-for-service beneficiaries aged ≥65 years with atrial fibrillation hospitalized for ischemic stroke (11/2011–10/2013) and subsequently admitted to a SNF were studied. Dabigatran (n=332) and rivaroxaban users (n=378) were compared in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Results of bias assessments are summarized in Supplementary Tables S6 and S7 . Overall, most cohort studies reported low risks of bias, while seven studies did not balance the confounding factors between groups, which had risks of comparability bias [ 8 , 25 , 30 , 31 , 39 41 ]. Three studies did not report the length of follow-up [ 27 , 31 , 35 ], and most studies did not show the lost follow-up rate, which had risks of outcome bias.…”
Section: Resultsmentioning
confidence: 99%
“…Results of bias assessments are summarized in Supplementary Tables S6 and S7 . Overall, most cohort studies reported low risks of bias, while seven studies did not balance the confounding factors between groups, which had risks of comparability bias [ 8 , 25 , 30 , 31 , 39 41 ]. Three studies did not report the length of follow-up [ 27 , 31 , 35 ], and most studies did not show the lost follow-up rate, which had risks of outcome bias.…”
Section: Resultsmentioning
confidence: 99%